Aluminum concentration range for the extrudability of ceramic pastes - Nancy Flores-Martinez; Fabien Remondiere; Jenny Jouin; Giuseppe Fiore; Stéphane Oriol; Sylvie Rossignol (Open Ceramics, 2022)
With the goal of developing refractory pastes to replace metal alloys used in turbine blades for Deep Space exploration, the French Space Agency, CNES, in collaboration with the Institute of Research for Ceramics, IRCER, has developed a preliminary research where dense alumina ceramics were formulated, printed and tested. This preliminary research will be the prelude to substituting by materials with more interesting creep properties at high temperature, for example, yttrium aluminum garnet, YAG. Since alumina is less expensive than YAG, preliminary tests were performed with alumina. These alumina pastes were 3D-printed by robocasting from very high solid loaded alumina pastes (>75 wt%), in the presence of organic additives, namely glycerol, PVA and ISOBAM 104. Several formulations of pastes were prepared, with the aim to obtain dense ceramic pieces. After, the alumina and the organic additives were mechanically mixed and the pastes were extruded with a commercial 3D printer. The best sample was obtained with a paste presenting an Al2O3 solid load of 79.37 wt% (63.5 vol%). A debinding step was performed afterwards to eliminate their organic content and the consolidation of the shaped pieces was finally achieved by sintering at 1700 °C. A % shrinkage of 8, 6.8 and 13.8 in the X, Y and Z-axes was measured, being one of the lowest values at 1700 °C compared to those in the literature.